China’s quest for global economic dominance - Łukasz Jureńczyk (Świat Idei i Polityki)
Strategic competition between the United States and China is the most crucial factor determining the stability of the global security system, including economic security. The dynamic economic growth of China in the 21st century and the rap[1]id enrichment of its society have garnered admiration, especially among the Global South, which China aims to lead. This progress occurred under relatively transparent rules established by the West under the leadership of the USA. However, China’s authoritarian government has used its effectiveness and agency to argue for its political and economic model. Currently, China faces significant development challenges, including a demographic crisis, increasing debt, and a weakening real estate market. Meanwhile, the United States is taking measures to limit China’s further economic growth, particularly in modern technologies and trade. China’s ability to overcome these barriers will determine whether it can achieve global economic dominance.